VD_FINDINFO Décision / 2014 / 58 vom 22. Januar 2014 - VD Tribunal cantonal (2014)
RISQUE DE FUITE, RISQUE DE COLLUSION, RISQUE DE RÉCIDIVE, DÉTENTION PRÉVENTIVE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH)